Association of domestic exposure to volatile organic compounds with asthma in young children. Issue 9 (27th August 2004) - Rumchev, K; Spickett, J; Bulsara, M; Phillips, M; Stick, S
Abstract : Aim: To investigate the association between domestic exposure to volatile organic compounds (VOCs) and asthma in young children. Methods: A population based case-control study was conducted in Perth, Western Australia in children aged between 6 months and 3 years. Cases (n = 88) were children recruited at Princess Margaret Hospital accident and emergency department and discharged with asthma as the primary diagnosis; 104 controls consisted of children from the same age group without an asthma diagnosis identified through the Health Department of Western Australia. Information regarding the health status of the study children and characteristics of the home was collected using a standardised questionnaire. Exposure to VOCs, average temperature and relative humidity were measured in winter and summer in the living room of each participating household. Results: Cases were exposed to significantly higher VOC levels (μg/m 3 ) than controls (p<0.01). Most of the individual VOCs appeared to be significant risk factors for asthma with the highest odds ratios for benzene followed by ethylbenzene and toluene. For every 10 unit increase in the concentration of toluene and benzene (μg/m 3 ) the risk of having asthma increased by almost two and three times, respectively. Conclusions: Domestic exposure to VOCs at levels below currently accepted recommendations may increase the risk of childhood asthma. Measurement of total VOCs may underestimate the risks associated with individual compounds.